2007
DOI: 10.3989/scimar.2007.71n2279
|View full text |Cite
|
Sign up to set email alerts
|

Emigration and retention of <i>Palinurus elephas</i> (Fabricius, 1787) in a central western Mediterranean marine protected area

Abstract: SUMMARY: This study describes the results obtained by applying the Arnason Schwartz multistate mark-recapture model to eight years of data collected in and around a small no-fishing marine protected area (MPA; 4 km 2 ) in the central western Mediterranean. From 1997 to 2004, a total of 4044 specimens of Palinurus elephas (Fabr., 1787) were tagged and 317 recaptured. The most parsimonious model which best explained the data variability was that of a temporally constant rate of apparent survival and movement in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 37 publications
2
22
0
Order By: Relevance
“…Analysis of recaptures of lobsters tagged and released inside the reserve indicated that the density gradient was caused by lobsters emigrating from the reserve (Goñi et al, 2006). Similar results using lobster mark-recapture data were obtained in western Sardinia (Follesa et al, 2007), and in Torre Guaceto MPA (Italy) for Diplodus spp. (Guidetti, 2006b).…”
Section: Exportation Of Biomass and Connectivitysupporting
confidence: 68%
“…Analysis of recaptures of lobsters tagged and released inside the reserve indicated that the density gradient was caused by lobsters emigrating from the reserve (Goñi et al, 2006). Similar results using lobster mark-recapture data were obtained in western Sardinia (Follesa et al, 2007), and in Torre Guaceto MPA (Italy) for Diplodus spp. (Guidetti, 2006b).…”
Section: Exportation Of Biomass and Connectivitysupporting
confidence: 68%
“…The small size of our study area (4 km 2 ) seems to have ensured, even in the first years of experimentation, the movement of lobsters from the IN zone to the OUT ones, at a rate that appeared constant throughout the 8-year period (Follesa et al, 2007). The similarity in the trends for the percentage increase in biomass inside and outside the area offers further strong support for the hypothesis of constant movement of Palinurus elephas between the two areas (even in the first year of experimentation), also confirmed by applying the Cormack-Jolly-Seber (CJS) model to the specimens tagged inside the area (Follesa et al, 2007).…”
Section: Cpuementioning
confidence: 96%
“…To date, many studies have been conducted in the Mediterranean Sea to assess the effectiveness of marine protected areas (Sanchez Lizaso et al, 2000) but few authors have assessed the response to the protection of spiny lobster populations in MPAs (Marin, 1987;Goni et al, 2001Goni et al, , 2006Follesa et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Roberts & Polunin 1991, Dahlgren & Sobel 2000, Schroeter et al 2001, Shears et al 2006. Not surprisingly, the abundance and often mean size of fished species is generally found to increase in reserves compared with adjacent fished areas (Edgar & Barrett 1997, Follesa et al 2007, Sonnenholzner et al 2009). More recently, however, the indirect effects of fishing on the trophic structure of reserve and fished communities have been considered with evidence of trophic cascades in several communities following the increase of predator densities in reserve areas (Scheffer et al 2005, Kramer & Heck 2007.…”
Section: Introductionmentioning
confidence: 99%